Schizotypy: a vulnerability factor for traumatic intrusions. - Holmes, E; Steel, C (2004)
Intrusive mental experiences occur within posttraumatic stress disorder (PTSD) and some psychotic disorders. Similarities in the phenomenology and content in the intrusions of both disorders have been noted. Currently there is little understanding of any common etiology in terms of information-processing styles. This study investigated predictors of analogue posttraumatic intrusive cognitions within a nonclinical sample, including schizotypy, dissociation, and trauma history. Forty-two participants watched a trauma video and recorded trauma-related intrusions occurring for 1 week. More reported intrusive experiences were associated with high positive symptom schizotypy. Our findings are discussed in relation to the possible role of trauma-related intrusions within psychotic disorders.